Challenges of diabetes prevention in the real world: results and lessons from the Melbourne Diabetes Prevention Study. Issue 1 (1st October 2015) - Dunbar, James A; Hernan, Andrea L; Janus, Edward D; Vartiainen, Erkki; Laatikainen, Tiina; Versace, Vincent L; Reynolds, John; Best, James D; Skinner, Timothy C; O'Reilly, Sharleen L; Mc Namara, Kevin P; Stewart, Elizabeth; et al.
Abstract : Objective: To assess effectiveness and implementability of the public health programme Life! Taking action on diabetes in Australian people at risk of developing type 2 diabetes. Research design and methods: Melbourne Diabetes Prevention Study (MDPS) was a unique study assessing effectiveness of Life! that used a randomized controlled trial design. Intervention participants with AUSDRISK score ≥15 received 1 individual and 5 structured 90 min group sessions. Controls received usual care. Outcome measures were obtained for all participants at baseline and 12 months and, additionally, for intervention participants at 3 months. Per protocol set (PPS) and intention to treat (ITT) analyses were performed. Results: PPS analyses were considered more informative from our study. In PPS analyses, intervention participants significantly improved in weight (−1.13 kg, p=0.016), waist circumference (−1.35 cm, p=0.044), systolic (−5.2 mm Hg, p=0.028) and diastolic blood pressure (−3.2 mm Hg, p=0.030) compared with controls. Based on observed weight change, estimated risk of developing diabetes reduced by 9.6% in the intervention and increased by 3.3% in control participants. Absolute 5-year cardiovascular disease (CVD) risk reduced significantly for intervention participants by 0.97 percentage points from 9.35% (10.4% relative risk reduction). In control participants, the risk increased by 0.11 percentage points (1.3% relative risk increase). The net effect for the change in CVD risk was −1.08 percentage points of absolute risk (p=0.013). Conclusions: MDPS effectively reduced the risk of diabetes and CVD, but the intervention effect on weight and waist reduction was modest due to the challenges in recruiting high-risk individuals and the abbreviated intervention.